Out of the past - Duff, Warren B. 1904-1973; Tourneur, Jacques 1904-1977; Mitchum, Robert 1917-1997; Greer, Jane; Douglas, Kirk 1916-2020 (Turner Home Entertainment, 2004)
Former private detective Jeff Bailey is trying to lead a quiet life, but his past comes back to haunt him and he finds himself framed for murder
Based on the novel "Build my gallows high" by Geoffrey Homes
Orig.: USA, 1947
Keywords: Homes, Geoffrey / 1902-1977 / Film and video adaptations; Homes, Geoffrey -- 1902-1977 -- Film adaptations.; Homes, Geoffrey -- 1902-1977 -- Television adaptations.; Homes, Geoffrey -- 1902-1977; Private investigators / Drama; Man-woman relationships / Drama; Feature films; Film noir; Films for the hearing impaired; Man-woman relationships -- Drama.; Private investigators -- Drama.; Feature films.; Verfilmung; Detektiv; Zweierbeziehung; Film; DVD-Video